Drug-induced hearing disorders: a disproportionality analysis of the FAERS database - Li, Baojian; Hu, Xiaoling; Yue, Zichen (Frontiers in Pharmacology, 2024)
Background: To evaluate and identify reports of adverse event related to hearing impairment with drugs approved in the past 20 years, to identify new adverse reaction signals related to hearing impairment that have not yet been reported, and to improve the safety of drug treatments. Methods: The adverse event report data from the FAERS database from the first quarter of 2004 to the fourth quarter of 2023 were retrieved. 'Hearing disorders' was used as the keyword to screen for drugs related to the adverse event. After standardizing the drug name and the adverse drug event name, the adverse event reports with hearing disorders as the main suspicion were collected, and the proportional imbalance algorithm was used to detect the potential signals of adverse event to hearing impairment of related drugs.The top five drugs with the highest number of reported adverse events to hearing impairment were: sacubitril/valsartan(2674)、 adalimumab(2479)、 etanercept(1834)、 tofacitinib(1812)、 apixaban(1600)， With the exception of adalimumab, the risk of hearing impairment is not mentioned in the instructions. The top five drugs for new signal strength are: pancuronium(n = 13